PERANCANGAN SISTEM MANAJEMEN WIFI BERBASIS WEB UNTUK PENGELOLAAN DATA PELANGGANDI MEGADATA NET - Marendra, Alfin Nur; Hidayat, Ahmad Tri (Program Studi Informatika Universitas Teknologi Sumbawa, 2024)
MEGADATA NET as a local internet service provider, requires a more effective customer data management solution to enhance operational efficiency and service quality. The manual recording system currently in use often leads to errors and delays in data management processes. This study designs a web-based management system utilizing PHP, MySQL, and the Laravel framework. The system facilitates customer data management, payment monitoring, and real-time report generation, thereby reducing reliance on manual record-keeping. It is expected that the implementation of this system will not only improve operational efficiency and data accuracy but also make it easier for customers to access information related to services and payment status. Additionally, this system is anticipated to increase customer satisfaction and strengthen data security.